Analysis of the safety compartment material of a light vehicle by multi-criteria method - Chamba, Edwin; Llanes, Edilberto; Cardenas, Andres; Vega, William; Rocha, Juan Carlos (Enfoque UTE, 2020)
There is a wide variety of materials with various properties available for designers to meet different design requirements. The objective of this study was to evaluate the properties of the relevant materials available in Ecuador through the multicriteria meth-od such as: Proportional complex evaluation (COP-RAS), Technique for the order of preference for similarity to real solution (TOPSIS), Optimization multi-disciplinary and compromise solution (VIKOR), in order to indicate which material would be a potential substitute for the original. It was concluded that 1045 steel is the best choice as a substitute for a safety compartment compared the base line the Aluminum-Magnesium alloy, considering that, despite being a light material, has low resistance to impact forces.